O processo de formulação da estratégia: um estudo de caso longitudinal sobre o processo de construção das estratégias do Governo de Minas Gerais entre 1995-2011 - Mauro Cesar da Silveira (2013)
This thesis aims to question the assumptions of instrumental rationality of government planning process, from the analysis of the process of formulation of Integrated Development Plans Miners and their consequences Plans Multi-year Government Action in the period 1995-2011. In this, describes the environment in which plans were formulated, analyze its premises, processes of prioritization of strategies beyond the argumentative process contained in the Plans. Therefore, in this thesis we adopt the single case and longitudinal study, combined with the method of grounded theory and discourse analysis for the processing and analysis of data. From this study, the author defends the government strategic planning as a socially constructed ritual that seeks to legitimize government decisions. Thus, the planning process as a political institution sufficiently adaptable, and cohesive complex should be able to absorb and organize the participation of interest groups in an arena able to watch the fight between these interests without the conflict ends in chaos. In this perspective, the process of strategic planning government should allocate resources and values in favor of the company, in a joint effort to produce and implement public policies in a democratic manner. The author argues that the process of construction of government planning is a social construction. As such, it often relies on symbols and rituals whose meanings, to some extent, are socially shared. In the construction of this discourse legitimizing the government strategic planning process becomes a space of competition between discourses and regimes of truth. Among the symbols used in the construction of plans, in order to obtain legitimacy, some stood out: the efficiency of the private sector, technical rationality, the hero-leader and the political importance of Minas Gerais. In addition to the symbols, the government planning process is marked by several rites, for example, social participation or the participation of the legislature, which aim to confer legitimacy. We also observe that these rituals are extremely formal participation and do not produce effective participation. Rather, what is observed in the studied processes is that the formation of these plans is directly linked to a very small number of people who are part of the executive branch. Thus, the governmental strategic planning process should be viewed as a series of events that depend on a complex chain of reciprocal interactions, and often this chain can not be predicted or controlled. Thus, it presents a critique of strategic planning "classic", with their diagrams and their graphs, which transmits an ideal that everything will be fine as long as the rules are followed and that good management practices are respected. What is observed in the processes studied is a fluid process, marked by the comings and goings. In the formulation of strategic planning government of Minas Gerais and its instruments verified the existence of separate, simultaneous streams. On the one hand, discusses the vision, the analysis of the external environment, the priority goals and strategies, on the other, are formulated programs.